The Effect of Kepok Banana Flour Subtitution on the Quality of Chocochips Cookies - Santri, Ranny; Holinesti, Rahmi (Universitas Negeri Padang, 2022)
This study aims to analyze the quality of chocochips cookies produced from substitution of banana kepok flour as much as 15%, 30%, and 45% which includes shape, color, aroma, texture and taste. This type of research is a true experiment using the Completely Randomized Design (CRD) method and carried out with 4 treatments and 3 repetitions. This research was carried out in October-November 2021 at the Catering Workshop, Department of Family Welfare, Faculty of Tourism and Hospitality, Padang State University. The object of this research is chocochips cookies with the replacement of wheat flour with banana kepok flour as much as 15%, 30%, and 45% on the quality of chocochips cookies. The types and sources of data used are primary data obtained directly from 5 expert panelists by filling out the organoleptic test format on the quality of chocochips cookies with banana kepok flour. Data analysis used Analysis of Variance (ANOVA). If there is a significant effect, the Duncan test will be carried out. The results showed that the substitution of banana kepok flour had no significant effect on the quality of the shape, color, aroma, and taste of chocochips cookies with banana kepok flour. Meanwhile, a significant influence is found on the quality of the texture of the chocochips cookies with banana kepok flour. The results of the quality test of the best kepok banana flour chocochips cookies were in treatment (X1) with 15% kepok banana flour substitution.